Structural and Morphological Study of Magnesium Phosphate from Bittern by pH Treatment and Addition of Sodium Phosphate - Dyah Suci, Perwitasari; Evlyansa Bunga Rizka Ananda; Dodik Hendra Saputra; Nur Aini Fauziyah (Chemistry Department, The University of Brawijaya, 2025)
This study focuses on the study of the structure and morphology of magnesium phosphate produced through the separation process of magnesium minerals from bittern waste through the precipitation method. This process involves the precipitation of magnesium phosphate (Mg₃(PO₄)₂) by varying the pH of the solution to 8.0, 8.5, 9.0, 9.5, and 10.0, and by adding Na₃PO₄ with varying concentrations of 5, 10, 15, 20, and 25 %. This chemical reaction produces magnesium phosphate precipitates were analyzed to determine their structural and morphological characteristics. The results showed that pH 9 and Na₃PO₄ concentration of 15 % are the optimal conditions for producing magnesium phosphate with the highest yield (25.1 %). Structural and morphological analysis show that magnesium phosphate exhibits an elongated shape with non-uniform size distribution, while the NaCl residue formed as a by-product had a typical cubic morphology. The presence of NaCl residue corresponds to the expected reaction mechanism, therefore, additional purification steps were needed to increase the purity of the final product. Overall, the results of this study indicate the potential for utilizing bittern as an alternative raw material for the synthesis of value-added magnesium phosphate, particularly for agriculture or industrial applications.